ExecutionFlow: a tool to compute test paths of Java methods and constructors - Niemiec, William; Silva, Keslley; Cota, Erika (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Calculating the code coverage of a test suite depends on the identification of the executed test paths. Available code coverage tools are limited to a few basic tracing strategies and do not provide this information as proper test paths, precluding its use in further analyses. We present ExecutionFlow, a solution to trace executed test paths in Java code. The tool is based on the use of a debugger, aspect-oriented programming, and a testing framework. Through empirical validation we show that it is possible to obtain the test path from several methods and constructors, including high complexity ones. Video demonstration:  https://youtu.be/2W5BjVuc6fw